(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
The article examines the emotional means of language in the function of oral expression of the critical attitude of the author of English essay texts to the transmitted message. Based on the work of local and foreign linguists, the author of the article determines the categorical status of emotion and connects the concept of "emotion" with the corresponding category of "expressiveness". Systematization of language tools aimed at verbal expression of feelings is carried out based on the tasks achieved through their use.